Development of anti-hepatitis B virus core antigen biosensor using gold nanoparticle-decorated reduced graphene oxide - Abd Muain, Mohamad Farid (2019)
The presence of antibody against hepatitis B virus core antigen (anti-HBcAg) in blood serum indicates that the patients have been exposed to hepatitis B virus (HBV), and can be used as a biomarker for occult hepatitis B virus infection (OBI). Currently, the diagnostic applications targeting HBV infection are time-consuming, lab-based and not practical for fast point-of-care (POC) diagnostic. Therefore, future development of HBV infection detection systems for rapid, and highly sensitive method is imperative. This work focused on the development of an immunosensor for the detection of anti-HBcAg through the use of hepatitis B virus core antigen (HBcAg) as the main bioreceptor. This bioreceptor was immobilized onto the gold nanoparticles-decorated reduced graphene oxide (rGO-en-AuNPs) which possesses excellent electrical conductivity and ability to hold highest amount of HBcAg compared to graphene oxide (GO) and reduced graphene oxide (rGO-en). Fabrication of rGO-en-AuNPs employed ethylenediamine as the reducing agent of GO, and also act as agent to hold the gold nanoparticles (AuNPs) in place on the rGO. All four types of characterization which are field emission scanning electron microscope (FESEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) and Raman spectroscopy confirmed that GO had been reduced and AuNPs had successfully incorporated onto the rGO-en. Then, the assembled HBcAg-immobilized rGO-en-AuNPs on the screen-printed electrode (SPE) was allowed to undergo impedimetric detection of anti-HBcAg with the concentration ranging from 3.91 ng mL−1 to 125.00 ng mL−1, with antibody against estradiol (anti-estradiol) and bovine serum albumin (BSA) as the interferences. Upon successful detection of anti-HBcAg in spiked buffer samples with the limit of detection (LOD) of 3.80 ng mL−1 at 3 σ m−1 (linear regression equation of ΔRct = 0.0261[anti-HBcAg] + 6.421 (R2 = 0.982)), impedimetric detection of the antibody was then further carried out in spiked human serum samples. In the presence of interferences, and the human serum samples, the LOD were calculated to be at 3.88 ng mL−1 at 3 σ m−1 (linear regression equation of ΔRct = 0.0315[anti-HBcAg] + 6.309 (R2 = 0.971)), and 5.60 ng mL−1 at 3 σ m−1 (linear regression equation of ΔRct = 0.0345[anti-HBcAg] + 6.467 (R2 = 0.961)) respectively. The electrochemical response in all anti-HBcAg detection showed a linear relationship between electron transfer resistance (Rct) and the concentration of anti-HBcAg. In contrast, no cross reaction observed when the HBcAg-immobilized rGO-en-AuNPs was allowed to react with non-related antibody. This stage of biosensor development is a primary platform for further study in producing the anti-HBcAg immunosensor prototype that possesses higher and better selectivity and specificity in the future. Further miniaturization works are possible to be carried out given the chosen method of electrochemistry.